Successful Partnerships: A Matter of Experience? - Grotenhuis, Frits D. J. (UI Scholars Hub, 2010)
Statistics indicate that most mergers and acquisitions are not very successful. At the same time, similar reasons for success and failure have been reported over the past decades by different scholars. Frequent mentioned reasons are related to finansial or legal issues during the pre-merger phase and cultural or integration issues during the post-merger phase. This far, hardly any study examined the learning effect of previous mergers and acquisitions experiences. This paper focuses on the post-merger integration phase of mergers and acquisitions, and the learning elements. First results indicate that managers can learn from previous experience and thus increase changes for success of partnerships. Future studies could further explore 'best practices' of how to organize and facilitate the learning process of mergers and acquisitions. Further, concerning managerial experiences, it would be interesting to discern between more geral lessons, and context-spesific lessons of mergers as well as of other kinds of strategic partnerships.